Laboratory and Field Aging Effect on Bitumen Chemistry and Rheology in Porous Asphalt Mixture. Issue 3 (March 2019) - Jing, Ruxin; Varveri, Aikaterini; Liu, Xueyan; Scarpas, Athanasios; Erkens, Sandra
Oxidative aging takes place in bituminous materials during the construction and service life of asphalt pavements and has a significant effect on their performance. In this study, porous asphalt cores were obtained from field test sections each year from 2014 to 2017. The evolution of the properties of the field cores and the recovered bitumen with time was investigated. Cyclic indirect tensile tests were performed to determine changes in the mechanical behavior of porous asphalt due to aging. Additionally, bitumen was extracted and recovered from 13 mm slices along the depth of the cores. The rheological and chemical properties of the recovered bitumen, as well as that of original bitumen aged in standard short- and long-term aging protocols, were investigated by means of dynamic shear rheometer and Fourier transform infrared spectrometer. The results show that the degree of aging is spatially dependent, resulting in a stiffness gradient within the asphalt layer. Moreover, the results demonstrate a weak relation between field aging and the standard laboratory aging protocols.